Effect of carbon quantum and graphene quantum dots on efficiency of dye-sensitized solar cells - Muhammad, Nazalea Yazmin (2020)
Dye Sensitize Solar Cell (DSSC) is a photo electrochemical cell that has a comparative mechanism as photosynthesis in nature with effective electron separation, enabling the cell to perform well under overcast condition. In any case, unfortunate recombination response of generated electrons with oxidized species has limited the advancement of high performing DSSC. The recombination process can be limited by integrating photoanode film with a thickness smaller than electron diffusion length. However, a very thin photoanode film has low capability to confine light and anchor dye molecules. This study aims to improve the performance of DSSC through applying advanced material, Graphene Quantum Dots (GQDs) and Carbon Quantum Dots (CQDs) in the photoanode. Both known to have high electron mobility and high surface area with good photoluminescence properties make it a right decision to choose it as enhancer for DSSC. Photoanode was immersed in the enhancer solution in a series of adsorption time. This is to identify the optimum adsorption time for the enhancer. It has been observed that adsorption of GQDs of 48 hours achieved the highest efficiency, which is at 4.53%. Besides that, the value of short circuit current (JSC), open circuit voltage (VOC) and fill factor (FF) is 12.26 mA cm-2, 0.72 V, 0.55 sequentially. Meanwhile, the adsorption time of CQDs reached the highest efficiency, which is at 3.50% also at 48 hours. In addition, the value of short circuit current (JSC), open circuit voltage (VOC) and fill factor (FF) is 10.01 mA cm-2, 0.68 V, 0.51 consequently. Both enhancers have been observed to successfully enhance the efficiency and performance of the cell with conventional DSSC fabricated in this laboratory.